(untitled) (Research, Society and Development, 2025)
Objective: To report the experience of physical therapy assistance to trauma and orthopedic patients at CER-IV in the teleconsultation and telemonitoring form during the context of COVID-19 pandemic. Methodology: From March to July 2020, after the guidelines of social isolation, teleconsultation and telemonitoring services were carried out, through the Web Conference platform, authorized from March 2020 by the Federal Council of Physiotherapy and Occupational Therapy - COFFITO. The consultations were carried out synchronously, lasting about 30 minutes, weekly, and the access through the address of the online room forwarded to their device, according to the scheduled time. In the meetings, exercises performed that could be reproduced throughout the week, aiming mainly at maintaining or gaining strength, range of motion and relief of acute or chronic pain. Results and discussion: The patients assisted by telemonitoring were previously seen at CER-IV, from the post-trauma and amputee rehabilitation sectors. Challenges were faced in adapting to the new modality, however, progressive adaptation by professionals and patients, which advance advancement and continuity in care. Final considerations: Remote mode is not a substitute for conventional physical therapy, however, in a scenario where face-to-face meetings would not be possible, physical therapy telemonitoring for trauma patients at CER-IV was effective and met the demands of the moment, and could be used as an option for continuity of assistance since the face-to-face format of follow-up is not possible.